Pengaruh Promosi Melalui Marketplace Shopee Terhadap Keputusan Impluse Buying Pada Pebgguna Aplikasi Shopee di Kabupaten Karawang - Bintang Cardova Zackyan; Endang Taufiqurahman (Peneliti.net, 2023)
This study uses a quantitative method with a descriptive and verification approach. With a sample of 400 respondents, 1,730,472 people were taken from a population aged 15-17 years in Karawang district using a non-probability sampling technique. As well as using path analysis and hypothesis testing using the t test and f test. By using Microsoft Excel tools, Method of Successive Interval (MSI), and the SPSS application version 25. Based on the results of the analysis that has been carried out, this study proves that the description of Promotions Through the Shopee Marketplace, Discounts and Impulse Buying Decisions for Shopee application users in Karawang Regency is included in the good category. Promotion variable through the Shopee Marketplace with an average score of 1,669.3 out of a maximum score of 2,000, Discount variable with an average score of 1,693.17 out of a maximum score of 2,000, Impulse Buying Decision variable with an average score of 1,691.4 out of a score a maximum of 2,000. The correlation coefficient between the Promotion Through Shopee Marketplace and Discount variables obtained a value of 0.677 which means that it has a strong, positive and significant correlation level between Promotion Through the Shopee Marketplace and Discounts. The partial effect of promotions through the Shopee Marketplace on Impulse Buying Decisions is 30%, while the partial effect of Discounts on Impulse Buying Decisions is 31.7%. So it can be stated that discounts contribute more to Impulse Buying Decisions compared to Promotions Through the Shopee Marketplace. The simultaneous effect of promotions through the Shopee Marketplace and Discounts on Impulse Buying Decisions is 61.7% while the remaining 38.3% is another variable not examined in this study.